Durable Complete Radiological Response to Nivolumab in Two Heavily Pretreated Western Elderly Patients With Metastatic Gastric Cancer: A Case Report - Tirino, Giuseppe; Petrillo, Angelica; Pompella, Luca; Pappalardo, Annalisa; Laterza, Maria Maddalena; Panarese, Iacopo; Sabetta, Rosalaura; Franco, Renato; Galizia, Gennaro; Ciardiello, Fortunato; De Vita, Ferdinando (Frontiers in Oncology, 2020)
Background: The prognosis of patients with advanced gastric cancer remains overall poor despite some recent innovations and the development of new therapeutic approaches. Current European guidelines do not recommend any specific treatment for patients with advanced gastric cancer refractory to two or more previous chemotherapy regimens, making this setting "orphan". Immunotherapy is quickly evolving also for this malignancy even if with controversial results and the correct patient selection is still debated, especially for Western patients. The phase III ONO-4538-12 "ATTRACTION-2" represents the current landmark trial for the development of immunotherapy for pretreated Asian patients and led to the approval of Nivolumab in some Asian countries, while only previous phase trials are available for Caucasians. Complete radiological response is anecdotic and has never been described both in the pivotal trial both in the others with Western patients enrolled. Case presentation: We report two cases of heavily pretreated Western elderly patients with metastatic gastric cancer who experienced durable complete radiological response to Nivolumab “off label” (more than 20 months to date) in a clinical practice context. Molecular analysis of potential predictive factors has been performed (PD-L1, EBV, MSI and TMB) on primary tumor sample. Conclusions: Despite the lack of evidence for Western patients and the controversial outcome with the use of checkpoint inhibitors in previous settings, immunotherapy may dramatically change the prognosis and the natural history of pretreated Western metastatic gastric cancer, in a correctly selected population. Microsatellite instability and tumor mutational burden may be realiable predictive factors also for Caucasians. There is an urgent need for a change in clinical practice also for this "orphan" patients and more efforts are needed in order to clarify the role of predictive factors for a correct patient selection and better chances of survival for this awful malignancy.